A study on different techniques of restoration of fire damaged reinforced concrete flexural members. (12th June 2017) - Anasco Bastin, Danie Roy; Sharma, Umesh Kumar; Bhargava, Pradeep
Abstract : Purpose: The main aim of this research was to investigate the effectiveness of various strengthening techniques in restoring the structural performance of reinforced concrete (RC) beams damaged by elevated temperatures. Design/methodology/approach: Three different strengthening techniques, namely, high-strength fibre reinforced concrete (HSFRC), ferrocement (FC) jacketing and externally bonded fibre-reinforced polymer (FRP) were used. Series of RC beams were casted, heated, strengthened and tested to investigate the influence of various variables. The variables of the study were type of strengthening and level of heat damage. Findings: Externally bonded FRP was found to be the best among the various techniques, especially with respect to strength and stiffness restoration. On the contrary, the FRP strengthening was not that effective in restoring the energy absorption capacity of beams compared to HSFRC and FC techniques of strengthening. The chosen strengthening techniques were able to restore the failure mode of beams to flexural failure, which was found to have changed to shear failure in case of heated unstrenghthened beams. Originality/value: This research program has contributed to the fundamental understanding of designing post fire retrofit solutions for RC beams.